2021
DOI: 10.1002/2050-7038.12997
|View full text |Cite
|
Sign up to set email alerts
|

Power quality improvement in distribution system using distribution static compensator with super twisting sliding mode control

Abstract: Nowadays, power quality (PQ) issues are gaining considerable attention to both electrical utilities and end-users as they are causing significant financial losses to industrial customers. Among PQ issues, voltage sag and swell are the most important and frequently occurring problems for sensitive load. Voltage sag/swell can be mitigated using a distribution static compensator (DSTATCOM), which is fast, effective, and flexible custom power device. Its performance mostly depends upon the designed control scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…It is a second order SMC which generates the continuous control signal and ensures the chattering free response with finite time convergence (Levant, 1993). In the control structure of STSMC as shown in Figure 4, the combination of nominal control law and the discontinuous control law gives the equivalent control law which is given by (Feng and Fei, 2018; Ullah and Hanif, 2021):…”
Section: Control Structure For Hybrid Energy Storage Systemmentioning
confidence: 99%
“…It is a second order SMC which generates the continuous control signal and ensures the chattering free response with finite time convergence (Levant, 1993). In the control structure of STSMC as shown in Figure 4, the combination of nominal control law and the discontinuous control law gives the equivalent control law which is given by (Feng and Fei, 2018; Ullah and Hanif, 2021):…”
Section: Control Structure For Hybrid Energy Storage Systemmentioning
confidence: 99%
“…The presented controller takes into account several variables brought on by changes in load, the microgrid battery's state of charge, and power tariffs based on the availability of electricity in microgrids. Authors in [16] have shown a fused control scheme for the VSC of DSTATCOM. It is based on the second-order super twisting algorithm and sliding mode control (SMC), and it effectively eliminates the effects of voltage sag/swell and compensates for active and reactive power in distribution systems.…”
Section: Introductionmentioning
confidence: 99%
“…So accomplishing this task can make use of PV panels very effective and it will largely reduce the use of non-renewable sources which will have such a huge impact on mankind's lifestyle that it can save a huge amount of money and world resources. However high installation cost and getting lower efficiency are still the challenges that are faced nowadays by researchers [1,2]. Solar energy plays a vital role in the development of a country.…”
Section: Introductionmentioning
confidence: 99%